2006
DOI: 10.1007/s00467-006-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of delayed development on the quality of life of adults with end-stage renal disease since childhood

Abstract: Little is known about the impact of the course of life of children with end-stage renal disease (ESRD) on their quality of life in adulthood. We therefore assessed the course of life of adult patients with onset of ESRD at an age of <15 years between 1972 and 1992 and compared it with that of the general population. Furthermore, we explored how course of life is associated with quality of life (QoL) in young adulthood. A total of 75 young adult patients who had had ESRD since childhood, aged between 20 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 19 publications
1
50
2
Order By: Relevance
“…Methodological shortcomings in the studies reviews included relatively small sample and subgroups sizes or subgroups were uneven in numbers (Goldstein et al, 2006;Grootenhuis et al, 2006;Groothoff et al, 2005;McKenna et al, 2006;Nicholas et al, 2011;Snethen et al, 2001;Snethen et al, 2004;Water, 2008). Also, some researchers (Goldstein et al, 2006;Grootenhuis et al, 2006;Groothoff et al, 2005;McKenna et al, 2006) did not indicate calculation of sample size so that adequacy cannot be assessed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Methodological shortcomings in the studies reviews included relatively small sample and subgroups sizes or subgroups were uneven in numbers (Goldstein et al, 2006;Grootenhuis et al, 2006;Groothoff et al, 2005;McKenna et al, 2006;Nicholas et al, 2011;Snethen et al, 2001;Snethen et al, 2004;Water, 2008). Also, some researchers (Goldstein et al, 2006;Grootenhuis et al, 2006;Groothoff et al, 2005;McKenna et al, 2006) did not indicate calculation of sample size so that adequacy cannot be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Grootenhuis et al (2006) and Groothoff et al (2005) studied the late physical, social, and psychosexual effects of childhood onset ESRD among Dutch adults using quality of life and other measures. Grootenhuis et al (2006) found that their sample of 39 men and 36 women between 20 to 30 years of age had reached fewer milestones in the areas of autonomy (i.e. at home or outside of home), social (i.e.…”
Section: Children Esrd and Dialysismentioning
confidence: 99%
See 2 more Smart Citations
“…These patients presented a delayed social, psychological and sexual development, in addition to decreased autonomy when adults. 27,28 In the study of Rosenkranz et al,…”
mentioning
confidence: 99%